2015
DOI: 10.5897/jpp2015.0370
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of the decoction and macerated leaves of Rhamnus alaternus L. on rats exposed to carbon tetrachloride

Abstract: The plant of Ramnus alaternus L. (Rhamnaceae) has been object of many therapeutic indications for traditional medicine. Many studies have showed a hepatoprotective activity of R. alaternus L. The objective of this study was to compare the hepatoprotective activities of decoction and macerated R. Alaternus L. leaves extracts on rats initially exposed to carbon tetrachloride CCl 4 (1 ml/kg). The macerated leaves (250 mg/kg body weight) showed a highly significant hepatoprotective activity (p < 0.01) expressed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Campbell et al, (2019) reported essential oils from the leaves of R. prinoides of which 4-hydroxy-4methyl-2-pentanone and ethyl 4-ethoxybenzoate score more than 85% and exhibited significant anti-biofilm activity (113). In a related study, Chouitah et al, (2012) (GOT),Glutamic pyruvic transaminase (GPT) and total bilirubin and significantly attenuated the deleterious histopathologic changes in the liver after carbon tetrachloride (CCl4)-intoxication (14).…”
Section: Essential Oilsmentioning
confidence: 97%
See 2 more Smart Citations
“…Campbell et al, (2019) reported essential oils from the leaves of R. prinoides of which 4-hydroxy-4methyl-2-pentanone and ethyl 4-ethoxybenzoate score more than 85% and exhibited significant anti-biofilm activity (113). In a related study, Chouitah et al, (2012) (GOT),Glutamic pyruvic transaminase (GPT) and total bilirubin and significantly attenuated the deleterious histopathologic changes in the liver after carbon tetrachloride (CCl4)-intoxication (14).…”
Section: Essential Oilsmentioning
confidence: 97%
“…Summary of pharmacological activity of Rhamanus species is presented in Table 3 below. Extract reduced levels of alkaline phosphatase (ALP), Glutamic oxaloacetic transaminase (GOT), Glutamic pyruvic transaminase (GPT) and total bilirubin and significantly attenuated deleterious histopathological changes in the liver (14) Anti-inflammatory R. alaternus ethanol Stem bark Carrageenaninduced rat paw edema assay extract exhibited anti-inflammatory activity with inhibition of 54.50% and 54.77% after 3 hr and 4 hr of treatment as compared the standard drug indomethacin (10 mg/kg) showed the inhibition of 50.46%, and 51.78% after 3hr and 4hr of treatment, respectively…”
Section: Antigenotoxic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Former authors observed that the methanolic maceration was better for extracting flavonoids than both aqueous maceration and aqueous decoction [21]. In another study, Berroukche and coworkers compared the same former extraction processes applied on leaves of Rhamnus alaternus to study their antioxidant and hepatoprotective effects [49]. The results of their investigation proved that leaves extracts obtained by maceration were better and more effective than those obtained by decoction in terms of bioactivity.…”
Section: Maceration and Decoctionmentioning
confidence: 99%